Mortality in rheumatoid arthritis: the impact of disease activity, treatment with glucocorticoids, TNFα inhibitors and rituximab. Issue 2 (29th November 2013) - Listing, Joachim; Kekow, Jörn; Manger, Bernhard; Burmester, Gerd-Rüdiger; Pattloch, Dagmar; Zink, Angela; Strangfeld, Anja
Abstract : Objectives: To investigate the impact of disease activity, the course of the disease, its treatment over time, comorbidities and traditional risk factors on survival. Methods: Data of the German biologics register RABBIT were used. Cox regression was applied to investigate the impact of time-varying covariates (disease activity as measured by the DAS28, functional capacity, treatment with glucocorticoids, biologic or synthetic disease modifying antirheumatic drugs (DMARDs)) on mortality after adjustment for age, sex, comorbid conditions and smoking. Results: During 31 378 patient-years of follow-up, 463 of 8908 patients died (standardised mortality ratio: 1.49 (95% CI 1.36 to 1.63)). Patients with persistent, highly active disease (mean DAS28 > 5.1) had a significantly higher mortality risk (adjusted HR (HRadj )=2.43; (95% CI 1.64 to 3.61)) than patients with persistently low disease activity (mean DAS28 < 3.2). Poor function and treatment with glucocorticoids > 5 mg/d was significantly associated with an increased mortality, independent of disease activity. Significantly lower mortality was observed in patients treated with tumour necrosis factor α (TNFα) inhibitors (HRadj =0.64 (95% CI 0.50 to 0.81), rituximab (HRadj =0.57 (95% CI 0.39 to 0.84), or other biologics (HRadj =0.64 (95% CI 0.42 to 0.99), compared to those receiving methotrexate. To account for treatment termination in patients at risk, an HRadj for patients ever exposed to TNFα inhibitors or rituximab was calculated. This resulted in an HRadj of 0.77 (95% CI 0.60 to 0.97). Conclusions: Patients with long-standing high disease activity are at substantially increased risk of mortality. Effective control of disease activity decreases mortality. TNFα inhibitors and rituximab seem to be superior to conventional DMARDs in reducing this risk.